The rise and fall of Pinus pinaster plantations in South Africa: from a significant commercial timber source to a declared exotic weed - De Ronde C. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
Although the species have been showing good growth potential in South Africa, with excellent tree form and timber qualities, it failed to maintain a significant portion of the local market. This was mainly because (a) its general growth rate was below that of other species in the Cape forest regions, such as Pinus radiata and (b) its superior timber quality was never appreciated in the form of a price rebate. The future of Pinus pinaster was further degraded because the species was declared as an invader in the natural fynbos vegetation, thus as an exotic weed. It is suggested that the species should be re-evaluated as a source of high quality timber, and that it is re-introduced in particular to the W. Cape and E. Cape forest regions, particularly where poor sandy soils occur, which are otherwise not suitable for commercial tree growing in plantation-form.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)